Development of the Comprehensive Simulation System for Autonomous Ships. Issue 1 (1st July 2022) - Minami, M; Kobayashi, M; Hikida, K; Kokubun, K
Abstract: In recent years, there has been a growing interest in autonomous ships, and efforts to realize autonomous ships are underway in Japan. Automated and unmanned ships are expected to improve safety by reducing accidents caused by human with the supports by the automated system. On the other hand, it is necessary to demonstrate that the autonomous ships are safely operated to implement the autonomous ships in society. The National Maritime Research Institute (NMRI) has been studying the evaluation method of safety of the autonomous ships and developing a simulation system as a tool for the evaluation. This paper introduces a comprehensive simulation system including a ship handling simulator, and the evaluation method using the simulation system.